THE CONTRIBUTION OF THE MOBILE VEGETABLE TRADERS - Josina Waromi; Maikel Baransano; Benyamin Korompis; Obadja A. Feneteruma; Agus Sumule (Socio-Economics/Agribusiness Department, 2022)
With trading activities, goods produced by producers can be directly enjoyed by consumers. Trading activities are carried out in all sectors, including the agricultural sector. Agricultural product trading activities can occur because there is a contribution from one of the traders in the trade chain, namely the mobile vegetable traders. However, research on the contribution of mobile vegetable traders in trading agriculture has yet to be widely carried out. Therefore, this study aims to examine the contribution of mobile vegetable traders in trading agricultural products. This study was done in Manokwari Regency, West Papua Province, in September 2021. The research method used is a descriptive method with a survey approach. The data obtained were processed by tabulation and examined descriptively. The results showed that the contribution of the mobile vegetable traders was divided into three groups. They have included the contribution to the local merchant farmers measured by the revenue that they got and the time for selling in the traditional market because agricultural products have been bought by the mobile vegetable traders to be traded again. The second contribution is to customers measured by the time, cost, and effort that should be used when the customers want to shop at traditional markets. The third contribution is to the family of mobile vegetable traders, which is measured by the income earned and used for the family. Information about the contribution of the mobile vegetable traders to their families, local farmers, and customers can be a consideration for the government to carry out appropriate empowerment for the mobile vegetable traders in creating independent and growing micro and small businesses.